THE ROLE OF THE FINANCIAL SERVICES AUTHORITY IN SUPERVISING THE HEALTH OF COMMERCIAL BANK - Septian Widiantoro (FH 15 UMY 058, 2015)
*58 Health bank supervision is one of role of the state effort to protect community funds and prevent massive economic crisis. The economic crisis occurs in Indonesia in 1996/1997 lead to closure of 16 banks. The crisis becomes an initial idea of establishment of Law Number 21 of 2011 on Financial Services Authority. The Financial Services Authority is independent institution which has function, duty and authority to regulate and supervise bank and non-bank institution. The role of the Financial Services Authority in supervising the health of bank is regulated on Law Number 21 of 2011 about Financial Services Authority. In supervise health bank, the Financial Services Authority uses Risk-Based Supervision method on 4 aspects, namely risk profile, good corporate governance, capital and profitability. The role of the Financial Services Authority in supervising the health of commercial bank are assessing heath bank level, examining health bank aspects, and conducting normal, intensive and special supervisions. The efforts of the Financial Services Authority to overcome bank with problem are with providing regulations, guidances, and mechanisms in intensive and special supervisions. The type of this research is a normative legal research with the Indonesian law approach through the regulations and policy that regulate it. By using a qualitative descriptive method, this research will describe the role of the Financial Services Authority in supervise health bank in detail related to regulation and policy. Finally, the result shows how the role and the effort of the Financial Services Authority in supervise bank health.